Comparison Of Milk Production Of Kankrej Cattle And Mehsana Buffaloes During Summer Stress - Patel, M.P.; Prajapati, K.B.; Joshi, N.A.; Panchasara, H.H.; Ankuya, K.J.; Patel , J.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The milk production capacity of Kankrej cattle and Mehsana buffaloes herd at Livestock Research Station was compared from the year 2010 to 2013 to know the influence of season on production of herd and to find out the superior herd of them. The herd average of Kankrej cattle remains significantly higher throughout the year especially in summer season in comparison to Mehsana buffalo.
Keywords: Seasonal influence; Kankrej cattle; Herd average; Mehsana buffalo